Navadna smreka - Picea abies (L.) Karsten - Jurc, Dušan (Gozdarski vestnik, 2006)
Presented are the most important diseases of trunk, wood and branches in Norway spruce. Annosus root rot of spruce is caused by Heterobasidion parviporum and H. annosum. The two fungi and the differences between them are presented, their anamorph, life cycle and the disease which they cause. The methods of determining the disease presence in the forest are described in detail, as well as silvicultural, chemical and biotic methods of its suppression. Stereum sanguinolentum is the most frequent pathogen of spruce wounds. Fomitopsis pinicola is a typical parasite of overaged and damaged old conifers and broadleaves, but above all it is the dominant saprob in forest. Gloeophyllum odoratum only rarely occurs as a parasite; it lives as saprob mainly in stumps.
Keywords: navadna smreka; Picea abies; bolezni rastlin; rdeča trohnoba; krvaveča slojevka; dišeča tramovka